Alkylgold(III) Complexes Undergo Unprecedented Photo‐Induced β‐Hydride Elimination and Reduction for Targeted Cancer Therapy. Issue 16 (21st February 2022) - Jiang, Jia; Cao, Bei; Chen, Yuting; Luo, Hejiang; Xue, Jiaying; Xiong, Xiaolin; Zou, Taotao
Abstract: Spatiotemporally controllable activation of prodrugs within tumors is highly desirable for cancer therapy to minimize toxic side effects. Herein we report that stable alkylgold(III) complexes can undergo unprecedented photo‐induced β‐hydride elimination, releasing alkyl ligands and forming gold(III)‐hydride intermediates that could be quickly converted into bioactive [Au III −S] adducts; meanwhile, the remaining alkylgold(III) complexes can photo‐catalytically reduce [Au III −S] into more bioactive Au I species. Such photo‐reactivities make it possible to functionalize gold complexes on the auxiliary alkyl ligands without attenuating the metal–biomacromolecule interactions. As a result, the gold(III) complexes containing glucose‐functionalized alkyl ligands displayed efficient and tumor‐selective uptake; notably, after one‐ or two‐photon activation, the complexes exhibited high thioredoxin reductase (TrxR) inhibition, potent cytotoxicity, and strong antiangiogenesis and antitumor activities in vivo. Abstract : A series of alkylgold(III) complexes containing glucose moieties were identified to undergo unprecedented photo‐induced β‐hydride elimination and reduction, leading to cancer‐selective cellular uptake, potent inhibition on thioredoxin reductase, up to 400‐fold increase of cytotoxicity in vitro, and strong antiangiogenic and anti‐tumor activities in two animal models.